Entre viver para si e viver para os outros: envelhecimento feminino e individualização - Soares, Cristiane Leal Rodrigues (2013)
This paper aims to reflect a comparative perspective in class processes of present female individualization in the experiences of older women belonging to middle segments and popular city of João Pessoa. Here I try to reveal old age as a period of building yourself. To do that, I make use of the approach on the transformations in the course of contemporary life, the values, representations and practices related to aging women. The central hypothesis of this paper is to present the experiences of aging women which are marked by processes of individualization, inexhaustible even with advancing age and showing that old age can be experienced as a phase of life in which it is building itself. I seek to understand, in this paper, as sociocultural and historical processes are updated in daily practices of the ladies and popular middle segments of our society, conceiving "ladies individualized." I start the assumptions that the individualization phenomenon constitutes a global trend in our society and that the possibility of joint relational and individualistic ideals is present both in the life experiences of individuals from middle segments, as the popular segments. In the case of research conducted for this thesis these individuals are respectively represented by elderly women living in the neighborhood of Bancários, and the community of Timbo in the city of João Pessoa. Because these joints are present in the daily lives of these women and how they present themselves in the course of their lives are questions that guided my thinking. I do not intend here to define how individualization process between older women and middle popular segments work, before long to discuss possibilities of processes of individualization and women from both of them reflect on the variations of the experiences of women aged above 60 as on their identities and representations of aging. The empirical data used in this thesis were qualitatively selected and come from direct observations, semi-structured interviews and stories of life trajectories, collected from 13 women aged between 60 and 70 years old. Seven of these women inhabit in Bancários, and the other in the community of Timbó. The characterization of these women, as belonging to the middle and popular segments, not only did so from the point of view of the place they occupy in the production structure. I analyze elements together as living space, conditions and styles of consumption, income and education, practices and habits of everyday life, trying to take into account concepts and tools to reflect both the objective aspects as those built to the level of culture. Were taken as the object of investigation the particular experiences of these women and sought to situate them in a spatial and temporal context, which includes not only their livelihoods but also the social interactions with other significant actors, capable of interfering in their social practices and daily experiences.